2000
DOI: 10.1038/sj.cdd.4400680
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the surface of apoptotic neutrophils: Implications for functional downregulation and recognition by phagocytes

Abstract: We have used a panel of monoclonal antibodies and lectins to examine the profile of surface molecule expression on human neutrophils that have undergone spontaneous apoptosis during in vitro culture. Neutrophil apoptosis was found to be accompanied by down-regulation of the immunoglobulin superfamily members PECAM-1 (CD31), ICAM-3 (CD50), CD66acde, and CD66b and the integrin-associated proteins CD63 and urokinase plasminogen activator receptor (CD87) that may alter the potential for adhesive interactions. Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
138
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(146 citation statements)
references
References 36 publications
6
138
1
1
Order By: Relevance
“…We observed that the latter are lost from cell surfaces during apoptosis, reflected by a decreased binding of MAL I. This finding is consistent with the observation of Hart et al 23 They found reduced binding of the sialic acid-specific lectins derived from Limulus polyphemus Maackia amurensis (MAL II), and Sambucus nigra to surfaces of apoptotic neutrophils when compared with viable cells. However, they did not observe an increased binding of the galactose recognizing lectin peanut agglutinin implying that complete desialylation caused by activated sialidases 24 did not represent a major carbohydrate modification event accompanying apoptosis.…”
Section: Calnexin and Er-tracker Co-localize Intracellular In Permeabsupporting
confidence: 93%
“…We observed that the latter are lost from cell surfaces during apoptosis, reflected by a decreased binding of MAL I. This finding is consistent with the observation of Hart et al 23 They found reduced binding of the sialic acid-specific lectins derived from Limulus polyphemus Maackia amurensis (MAL II), and Sambucus nigra to surfaces of apoptotic neutrophils when compared with viable cells. However, they did not observe an increased binding of the galactose recognizing lectin peanut agglutinin implying that complete desialylation caused by activated sialidases 24 did not represent a major carbohydrate modification event accompanying apoptosis.…”
Section: Calnexin and Er-tracker Co-localize Intracellular In Permeabsupporting
confidence: 93%
“…Cleaved caspase 3 flow cytometry was performed using the cleaved caspase-3 (Asp175) (5A1) rabbit monoclonal antibody (Cell Signaling, Hitchin, UK) according to the manufacturer's instructions. Flow cytometry using the BOB78 antibody at 1 in 100 and control antibody, also of IGM isotype (Sigma), was performed as described previously (Hart et al, 2000). The secondary antibody used was sheep anti-mouse IgG FITC (Dako, Ely, UK).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…When treated with glucose oxidase, 14% stained with annexin only, 9% with PI only, 58% with both and 19% with neither. On staining of cells with the BOB78 antibody, a surface marker of apoptosis (Hart et al, 2000), 8% stained with BOB78 only in the untreated sample, 6% with PI only, 6% with both and 80% with neither ( Figure 7A). On glucose oxidase treatment, 12% stained with BOB78 only, 18% with PI only, 45% with both and 253% with neither ( Figure 7A predominantly necrotic morphology and staining pattern.…”
Section: Analysis Of Huh7 Cell Response To Oxidative Stressmentioning
confidence: 99%
“…We have therefore undertaken further studies to characterize changes in the surface expression of carbohydrates and proteins associated with neutrophil apoptosis using dual-color flow cytometric analysis. 15,16 We now report the binding characteristics of a unique monoclonal antibody, termed BOB93, which displayed specific binding to apoptotic neutrophils.…”
mentioning
confidence: 99%
“…10 -12 We and others have previously shown that a number of alterations in the protein and carbohydrate composition of the plasma membrane are associated with apoptosis. 7,[13][14][15][16] It has also become apparent that apoptosis is associated with membrane alterations that confer specific binding of plasma proteins, with the potential for opsonization and regulation of subsequent phagocyte recognition. In particular, there is evidence that the collectin family of molecules, including complement component C1q, 17 mannose binding lectin, 18 and surfactant protein A, 19 exhibit specific binding to apoptotic cells.…”
mentioning
confidence: 99%